Mechanisms and Driving Forces of Safety Culture Co-Creation in the Forest Industry - Alina Linden; Henrik Barth; Pia Ulvenblad; Elin Karlsson; Rom Rwamamara (Safety, 2025)
The forest industry is one of the most dangerous workplaces worldwide, and although safety culture is recognized as important safety antecedent, there is still a theoretical and practical need for understanding how safety culture is co-created in the forest industry. To fill this gap, this article has the purpose of exploring mechanisms and driving forces of safety culture co-creation within the Swedish forest industry. Data is collected via on-site focus group interviews with 136 employees of a Swedish pulp- and paper factory. Data is analysed via thematic analysis. Results show that communication and engagement, safety training and knowledge sharing, reporting and risk management as well as integration of safety in daily operations are central safety culture co-creation mechanisms. Driving forces of safety culture co-creation driving forces are leadership commitment to safety, employee responsibility and collaboration, a continuous improvement mindset and work environment and psychosocial wellbeing. Central safety culture co-creation mechanisms and driving forces are identified in communication and interaction that span all individuals, teams, departments, organizational entities and hierarchical levels as basis for successful, sustainable and holistic safety culture co-creation.